Business plan jasa ekspedisi local shipment - Erwin Teddy Setiawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This business plan aims to provide a detailed explanation of the current supply chain management processes implemented at J&T Express as a reference for developing an improved supply chain management model. The goal is to shorten package delivery lead times, reduce operational costs, minimize the risk of package delays, increase courier and operator productivity, and reduce the likelihood of lost or damaged parcels in order to achieve higher customer satisfaction based on the evaluation of J&T Express key performance indicators in Central Jakarta as a reference. Business Plan ini bertujuan untuk menjelaskan secara terperinci proses Supply Chain Management yang sudah ada saat ini di JNT Express sebagai acuan untuk mengembangkan proses Supply Chain Management baru sehingga dapat, memperpendek waktu Lead Time pengiriman paket, menurunkan biaya operasional, mengurangi resiko paket stuck , meningkatkan produktifitas kurir serta operator dan juga mengurangi resiko Lost and Damage demi mencapai kepuasan pelanggan berdasarkan evaluasi Key Performance Indikator JNT Express di Jakarta Pusat sebagai acuan.